Conceptualising Habitus in Relation to Student’s Educational Experience A Critical Review of Empirical Studies - Bose, Nitika (JOURNAL OF INDIAN EDUCATION, 2018)
Education is a part of the larger social system, and recent researches have shown how inequalities and social stratification are replicated within schools. This critical review examines key empirical studies related to habitus, analysing the link between family, social class, teachers, schools and student’s educational experience drawing from Bourdieu’s Social Reproduction Theory. Bourdieu, in his argument, related scholastic development to nurture rather than nature. He stated that the ability and talent of an individual is determined by the time and cultural capital invested in them by their parents. According to Bourdieu, habitus is acquired in this way by internalising the external through primary and secondary socialisation. Bourdieu’s habitus as an analytic category holds relevance in educational research, and recent empirical studies have been built on the same. The present paper draws from recent findings of empirical studies, analysing the application of Bourdieu’s theorisation to highlight not only the ways in which individuals are shaped by their habitus, but also states that they are agents within their institutional environments— instead of simply replicating it, individuals contest, modify and negotiate while navigating through them.